Regulation of Early Lymphocyte Development via mRNA Decay Catalyzed by the CCR4-NOT Complex - Akiyama, Taishin; Yamamoto, Tadashi (Frontiers in Immunology, 2021)
Development of lymphocytes is precisely regulated by several mechanisms. In addition to transcriptional rates, post-transcriptional regulation of mRNA abundance contributes to differentiation of lymphocytes. mRNA decay is a post-transcriptional mechanism controlling mRNA abundance. The CCR4-NOT complex controls mRNA longevity by catalyzing mRNA deadenylation, which is the rate-limiting step in the mRNA decay pathway. mRNA decay, regulated by the CCR4-NOT complex, is required for differentiation of pro-B to pre-B cells and V(D)J recombination in pro-B cells. In this process, it is likely that the RNA-binding proteins, ZFP36L1 and ZFP36L2, recruit the CCR4-NOT complex to specific target mRNAs, thereby inducing cell quiescence of pro-B cells. A recent study showed that the CCR4-NOT complex participates in positive selection of thymocytes. Mechanistically, the CCR4-NOT deadenylase complex inhibits abnormal apoptosis by reducing the expression level of mRNAs encoding pro-apoptotic proteins, which are otherwise up-regulated during positive selection. We discuss mechanisms regulating CCR4-NOT complex-dependent mRNA decay in lymphocyte development and selection.